PENGEMBANGAN MODUL FISIKA BERBASIS KONTEKSTUAL PADA MATERI ALAT-ALAT OPTIK DALAM PEMBELAJARAN DI KELAS X SMAN 3 LUMAJANG - Septian Ari Kususa; Sudarti Sudarti; Pramudya Dwi Aristya (JURNAL PEMBELAJARAN FISIKA, 2017)
The purposes of this research are to know the validity and the effectivity of physics-based contextual modules on optical tools material. This type of research is the development, use research design Borg and Gall. The initial product design phase, a module will go through two stages of validation. The first validation phase is experts’ validation and is obtained the validity of 80,66% with valid enough degree of validity. The second validation phase is users’ validation and is obtained the validity of 88% with very valid degree of validity. The next research phase is the initial testing phase, at this stage will be known the audience ratings of the module. Audience validation involved 6 student and got the validity of 84,44% with very valid degree of validity. The last research phase is the research field to determine the effectiveness of the module. The result of the research field show that the module has been declared as effective modules for students, because they have got a score of 70 as much as 94,44%. Based on the result of this study, it can be concluded that the physics-based contextual learning modules developed valid and effective to be used in teaching in schools. Key word : contextual module, optical tools.